Basic and Clinical Pharmacology: International edition - Katzung, B. G. Bertram G.; Vanderah, T. W. Todd W. (International edition, 2021)
Master key pharmacological concepts and practices with the most comprehensive, authoritative guide available. Presented in full color and packed with hundreds of illustrations, Basic & clinical pharmacology is the wide-ranging, engaging guide students have counted on for decades. Organized to reflect the course sequence in many pharmacology courses and in integrated curricula, the guide covers the important concepts students need to know about the science of pharmacokogy and its application to clinical practice. This edition has been extensively updated to provide expanded coverage of transporters, pharmacogenomics, and new drugs. Delivers the knowledge and insight needed to exel in every facet of pharmacology!